Diseminasi Penarapan Sanitasi untuk Mengatasi Kesehatan Lingkungan Warga TKI di Johor Malaysia - Haris, Haris; Syamsidah, Syamsidah; Widodo, Slamet; Rauf, Bakhrani; Maru, Rosmini (Abdimas Indonesian Journal, 2024)
Environmental health has become a crucial issue in the Johor region of Malaysia, particularly in areas with high population density and limited access to sanitation facilities. This community service activity aims to disseminate the implementation of effective sanitation technology to improve the quality of environmental health, specifically for Indonesian migrant workers (TKI) living in Johor. The program focuses on educating about the importance of sanitation, introducing simple sanitation technologies, and providing assistance in applying hygiene practices in households. Through a participatory approach, Indonesian migrant workers in Johor are directly involved in outreach, training, and implementing community-based sanitation solutions. Evaluation is conducted to measure the program's impact on increasing community knowledge and changing behaviors related to sanitation. The results show a positive community response toward the importance of sanitation, as well as a significant reduction in environmental health issues, such as the transmission of environmentally-borne diseases. Disseminating the results through scientific publications and seminars is expected to serve as a reference for other regions with similar conditions, so that proper sanitation implementation can contribute to improving quality of life and public health